PROSES REPAIRING RACK SPAREPART MOBIL KHUSUS PART CRASH PAD MAIN ASSY - Nofa Erik Riyanto (Accurate: Journal of Mechanical Engineering and Science, 2023)
The car spare parts rack is one of the products ordered from PT. Y which is produced by PT. TH. Apart from that, PT. TH also accepts the shelf repair process if there is damage due to use. This research was conducted to find out the process of repairing car spare parts racks specifically for crash pad main assembly. The research method uses literature study and observation. Observations were carried out at PT. TH as the company in charge of repairing all rack spare parts from PT. Y. The shelf repair process generally includes steps to repair or restore the condition of damaged shelves, the process includes checking damage, measuring and cutting hollow steel for the shelf frame, welding process, cleaning welding marks, replacing shelf wheels, painting, installing parts. , installation of bases and roof racks, installation of rack covering mica, naming of racks and quality control process. Machines and equipment used in the shelf repair process include welding machines, grinders, hand drills, cutting wheels, compressors and anglers. This shelf repair procedure is in accordance with the SOP from PT. Y so that it can produce product improvements whose quality is guaranteed.